The Paradigm of Neil Robinson’s Thought on Islamic Philosophy among Orientalists - Supriyanto Supriyanto (International Journal of Social Science and Religion (IJSSR), 2023)
Al-Quran is God's revelation that has a position as a source of knowledge. It contains all matters of knowledge and supports the description of the existence of God and his majesty and the universe. Islam has a view of the concept of knowledge, which is closely related to God's involvement, the source of knowledge is believed to be God. This paper will examine several paradigms of Neal Robinson's thought in Islamic Philosophy among Orientalists, especially on the knowledge in the Qur'an. This is qualitative research with a library approach. The results of this study are that Neal Robinson's book consists of three main chapters, namely: Phenomenology; Text Chronology and Morphology; and Structure and Coherence. A text that has various roles and functions in the lives of its believers. Some of Robinson's studies are: how Muslims listen to the Qur'an, listening to the Qur'an; how do Muslims memorize the Qur'an, having the Qur'an by heart; and how the Qur'an is present in the daily life of Muslims, and the Qur'an in everyday life.